BIPOLAR DISORDER TYPE II: THE RELATIONSHIP BETWEEN INTERSTITIAL NEPHRITIS AND THE USE OF LITHIUM (CIPEEX, 2022)
BIPOLAR DISORDER (BD) IS A COMPLEX PSYCHIATRIC DISORDER, CHARACTERIZED BY DRASTIC CHANGES IN MOOD AND BEHAVIORAL DISORDERS, WHICH MAINLY AFFECTS YOUNG WOMEN, ON AVERAGE BETWEEN 25 AND 27 YEARS. IN THE PRESENT REPORT, WE AIMED TO REFER TO THE OCCURRENCE OF INTERSTITIAL NEPHRITIS, CAUSED BY THE TREATMENT OF BD BY LITHIUM. THUS, THE CASE OF A PATIENT ATTENDED IN A PRIVATE OFFICE REPORTING SUICIDAL IDEAS, DIAGNOSED WITH SEVERE DYSPHORIC SYNDROME, IS PRESENTED. SESSIONS OF COGNITIVE-BEHAVIORAL PSYCHOTHERAPY WERE INITIATED, AS WELL AS ITS DRUG TREATMENT, FOLLOWED BY SEVERAL CRISES AND UNSUCCESSFUL ATTEMPTS TO INTRODUCE LITHIUM AS A VIABLE OPTION. HOWEVER, AFTER A DECADE OF TREATMENT, THE PATIENT AGREED TO START ITS USE. EIGHT YEARS LATER, ACUTE INTERSTITIAL NEPHRITIS WAS DIAGNOSED, SECONDARY TO LITHIUM USE, REPLACING IT WITH CARBAMAZEPINE. THE PATIENT CONTINUED HER TREATMENT FOR ANOTHER FOUR YEARS, UNTIL SHE WAS REFERRED TO ANOTHER PROFESSIONAL IN A DIFFERENT LOCATION. MOREOVER, THE FINAL CONSIDERATION OF THE CASE IS THE CONSTANT NEED FOR MEDICAL EVALUATION WHEN NECESSARY THE USE OF SUCH MEDICATIONS, SINCE THE SIDE EFFECTS CAN BE HARMFUL TO PATIENTS.
Keywords: bipolar disorder; lithium; interstitial nephritis; carbamazepine